Interdisciplinary challenges for elucidating human olfactory attractiveness. (8th June 2020) - Ferdenzi, Camille; Richard Ortegón, Stéphane; Delplanque, Sylvain; Baldovini, Nicolas; Bensafi, Moustafa
Abstract : Many species use chemicals to communicate. In humans, there is increasing evidence that chemicals conveyed by the body are extremely important in interpersonal relationships. However, many aspects of chemical communication remain to be explored to fully understand this function in humans. The aim of this article is to identify relevant challenges in this field, with a focus on human attractiveness in the context of reproduction, and to put forward roadmaps for future studies that will hopefully extend to a wider range of social interactions. The first challenge consists in not being limited to body (mal)odours from the axilla. Preliminary data on how the odour of the face and head is perceived are presented. Second, there is a crucial need to increase our knowledge of the chemical bases of human chemical communication. Third, cross-cultural approaches must not be overlooked, because they have a major input in understanding the universal and culture-specific aspects of chemical communication. Fourth, the influence of specific cultural practices such as contraceptive and fragrance use is likely to be prominent and, therefore, needs to be well described. The fifth and last challenge for research projects in this field is the integration of different disciplines such as behavioural sciences, social sciences, neurosciences and microbiology. This article is part of the Theo Murphy meeting issue 'Olfactory communication in humans'.